Assessing the business dimensions of green IT transformation: a case of an Indian IT organisation. (15th January 2020) - Jayaprakash, Parvathi; Pillai, R. Radhakrishna
Green information technology (green IT) is the application of ecological consciousness to information technologies (ITs). This paper attempts to assess the business dimensions of green IT transformation in an organisation. The four business dimensions of green IT transformation, namely, economy, technology, people, and process are used in this study in the context of an Indian IT organisation. Though green IT transformation is unique for every organisation, a case of a particular organisation can provide a roadmap for other companies to develop such green IT transformation. Our analysis brings out the status of transformation in all four dimensions and recommendations are drawn to fine-tune the green IT transformation based on the findings.